2021
DOI: 10.11591/ijeecs.v24.i1.pp464-472
|View full text |Cite
|
Sign up to set email alerts
|

K-affinity propagation clustering algorithm for the classification of part-time workers using the internet

Abstract: There has been a significant increase in the number of part-time workers in the last 3 years. Data collected from sakernas BPS showed that the number of part-time workers was 125,443,748 in the second period of 2016. This number rapidly increased in 2017, 2018 and 2019 in the same period, by 128,062,746, 131,005,641, and 133,560,880 workers. Based on the increase in the last 3 years, East Java province has the highest number of part-time workers that use the internet. This research aims to determine the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
0
0
1
Order By: Relevance
“…Penelitian ini bertujuan untuk melihat gambaran umum NTP di Indonesia, yang kedua yakni menguraikan hasil clustering metode SOM dengan K-AP, dan terakhir untuk mengetahui hasil pengelompokan NTP terbaik antarat metode SOM dengan K-AP. Penelitian terkait metode SOM serta K-AP sudah diadakan oleh [11] dengan membandingkan metode clustering K-Medoids dengan SOM. Hasil cluster terbaik diperoleh dengan menggunakan metode SOM dengan nilai rasio standar deviasi yang lebih kecil daripada nilai rasio standar deviasi pada metode K-Medoids.…”
Section: Pendahuluanunclassified
“…Penelitian ini bertujuan untuk melihat gambaran umum NTP di Indonesia, yang kedua yakni menguraikan hasil clustering metode SOM dengan K-AP, dan terakhir untuk mengetahui hasil pengelompokan NTP terbaik antarat metode SOM dengan K-AP. Penelitian terkait metode SOM serta K-AP sudah diadakan oleh [11] dengan membandingkan metode clustering K-Medoids dengan SOM. Hasil cluster terbaik diperoleh dengan menggunakan metode SOM dengan nilai rasio standar deviasi yang lebih kecil daripada nilai rasio standar deviasi pada metode K-Medoids.…”
Section: Pendahuluanunclassified
“…The absence of reference variables in clustering process makes it can be used to assign labels to data group whose class is not known beforehand [9]. The distance between objects is carrying out the grouping and the shape is only affected by the size of the distances [10]. This process is calculated using the Euclidean distance, as follows.…”
Section: Clusteringmentioning
confidence: 99%
“…The three clustering methods produced significantly different standard deviation values, with the order from smallest to largest being k-affinity propagation, k-medoids, and k-means. It is concluded that the k-affinity propagation method proved to be the best with the smallest standard deviation [10].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations